Estimation of sesame mechanical harvesting losses in the mechanized rainfed areas of Eastern Sudan - Yousif, Lotfie A; Babiker, Ebtehag H (Gezira Journal of Agricultural Science; Vol 14 No 2 (2016), 2018)
Sesame ( Sesamum indicum L .) plays an essential role in Sudan economy, but its actual yield is low. Harvesting losses were considered as one factor which contributes to this low yield. The objectives of this research were to analyze and quantify sesame harvesting losses, and to estimate their economic values in the mechanized rainfed areas of Eastern Sudan. Four sesame cutter binders were tested, namely; BCS-I, BCS-II, Warta-2 and New life (a cutting and windrowing machine). The first two machines were self-propelled, the others were tractor operated. The study was conducted for three consecutive seasons, 2012 to 2014. Three types of loss were determined which were; pre-harvesting, machine (cutting and binding) and total losses. The collected data included; plant density, number of capsules per plant, number of fallen capsules before the introduction of machines and number of uncut and unbound capsules. The results showed that the overall average pre-harvesting loss was 0.6%. Cutting loss was 1%, 0.5%, 1.7% and 0.5% for BCS-I, BCS-II, Warta-2 and New life, respectively. Binding loss was between 2.8% for BCS-I and 3.3% for Warta-2, with an overall average of 3.1%. The average percent of machine and total harvesting losses were 3.2% and 3.8%, respectively. The estimated quantity of pre-harvest, machine and total losses were 1.32, 7.04 and 8.4 kg/ha, respectively. The results inferred that when half of the sesame area in Gedarif State is harvested by the tested machines, the estimated annual loss was 975 tons, which amounts to a total loss value of US$ 1.5 million, with an average US$ 10.1 loss value per hectare. The results concluded that the position of cutter bar with respect to the driver and the mechanism that prepare bundles for binding besides the knotting system are the machine features which affected mechanical harvesting losses of sesame crop.